Osteo-odonto keratoprosthesis: Innovative dental and ophthalmic blending - Jaswinder Kaur (Wolters Kluwer Medknow Publications, 2018)
Corneal diseases are among the major causes of global blindness, secondary to cataract. osteo-odonto keratoprosthesis (OOKP) is the ideal treatment for patients with end-stage inflammatory corneal diseases where a portion of tooth along with bone is used to support an optical cylinder to restore vision in such patients. OOKP surgery requires multidisciplinary approach involving dentists, ophthalmologists, and radiologists. Very less is known in dentistry about the role of the periodontium in the field of ophthalmology. This paper highlights OOKP indications, contraindications, surgical procedure, role of oral structures, advantages, and limitations.